Improving Students’ Speaking Ability Using Show and Tell Technique - Isra Alvionita; Munir Munir; Syarifah Faradiba (Journal of Excellence in English Language Education, 2022)
This research aimed to improve students' speaking abilities at SMAN 12 Makassar by employing the Show and Tell Technique. The researchers applied the pre-experimental method with one group pretest-posttest design. Class XI MIPA 3 which consisted of 36 students was chosen as a sample in this research using cluster random sampling. To collect data, the researchers used the interview as a speaking test to know the students’ speaking ability in terms of accuracy, fluency, and comprehensibility before and after administering the treatment. The result of this research indicated that the use of the Show and Tell Technique was effective in improving the students’ speaking ability. It was proved by the result of data analysis which showed that there was an improvement in the students’ scores in pre-test and post-test. In the post-test, the mean score of the student was 50.62. It was higher than the mean score in the pre-test which was 27.01. Therefore, the Show and Tell technique is effective to improve the students’ speaking ability in terms of accuracy, fluency, and comprehensibility.